Penerapan Online Collaborative Learning untuk Meningkatkan Technological dan Pedagogical Knowledge Bagi Guru PAUD - Susilaningsih, Susilaningsih; Oktaviani, Herlina Ike; Ulfa, Saida; Slamet, Taufik Ikhsan (Universitas Negeri Malang, 2023)
Abstract: The challenge for PAUD teachers in the 4.0 revolution era is to deal directly with the Alpha generation. Generation Alfa is the generation born in 2010 whose birth was exposed to technology. There needs to be an increase in pedagogic and technological abilities for PAUD teachers so that they can adjust the characteristics of their students. The purpose of this training activity is that teachers can apply collaborative online learning to increase technological and pedagogic knowledge. The training methods are lectures, role playing, and practice. The results of this activity were seen from the results of the pre-test and post-testt which showed that of the 30 trainees there were 3 teachers whose grades decreased while 27 teachers increased. This shows the success of this training in increasing pedagogic and technological knowledge for PAUD teachers.Abstrak: Tantangan Guru PAUD di era revolusi 4.0 adalah berhadapan langsung dengan generasi Alfa. Generasi Alfa adalah generasi yang lahir mulai tahun 2010 yang kelahirannya terpapar teknologi. Perlu adanya peningkatan kemampuan pedagogik dan teknologi untuk guru PAUD sehingga dapat menyesuaikan karakteristik peserta didiknya. Tujuan kegiatan pelatihan ini adalah guru dapat menerapkan pembelajaran online secara kolaborasi untuk menambah pengetahuan teknologi dan pedagogik. Metode pelatihannya adalah ceramah, role playing, dan praktek. Hasil dari kegiatan ini dilihat dari hasil pre-test dan postest yang menunjukkan dari 30 peserta pelatihan ada 3 orang guru yang nilainya menurun sedangkan 27 guru meningkat. Hal tersebut menunjukkan keberhasilan pelatihan ini dalam meningkatkan pengetahuan pedagogik dan teknologi untuk guru PAUD.